Behaviors of farmers towards pig diseases in Hung Yen Province - Nguyen Thi Thu Huyen; Pham Van Hung (2016)
This paper investigates disease situation and responses of farmers to pig diseases in Hung Yen province. Descriptive statistics, classification, comparison, T test and analysis of economic efficiency are utilized. It has been found that some common diseases occur more often at piglet weaning stage in comparison to other growth stages. When common diseases occur, farmers usually treat by themselves. Therefore, training on skills for diagnosis and treatment of common diseases should be offered for farmers. In addition, training to improve skills for local veterinarians should be also implemented because they do not only sell veterinary drugs to farmers but also give farmers technical advices. Propaganda and regulations to mitigate and prevent the sale of pigs died of diseases should be taken to limit the spread of disease in the local pig herds. In addition, a mass campaign to improve farmers’ disease preventive practices such as pig barn sanitation, vaccination and action to disease occurrence in the household and the commune should also be carried out.